Effect of pH on Green Synthesis of Reduced Graphene Oxide Using Lemon Extract and Application of Fe3O4/RGO nanocomposites for the removal of Pb (II) from aqueous solution - Maryam Ghasemi; Javad Azimi-Amin (Journal of Water and Environmental Nanotechnology, 2022)
Here, graphene oxide was synthesized and reduced by lemon extract (source of vitamin C) in an aqueous solution under different pH (3 and 10). The lemon extract was prepared using a solvent-free method. The proposed mechanisms for the reduction of GO may be due to the nucleophilic attack of oxygen anion of ascorbic acid to the epoxy or hydroxyl groups of GO sheets. Based on Raman spectra, with increasing the solution pH, the repair of the graphitic sp2 domain of the RGOs decreased. Reduced graphene oxide was successfully used to synthesize Fe3O4/RGO nanocomposite and remove Pb ions from aqueous media. The obtained Fe3O4/RGO nanocomposite was characterized by XRD, FTIR, SEM, and BET analysis. Based on these characterization techniques, reduced graphene oxide is distinguishably coated by Fe3O4 nanoparticles. The effect of different parameters: contact time (1-60 min), initial lead concentration (25-200 mg/L), adsorbent dosage (0.01-0.07 g), and the solution’s initial pH (1-8) on the removal of lead ions was studied using batch-scale tests. The maximum lead ion removal was achieved up to 90 % for Pb ions, respectively at optimum operating conditions viz. pH 5, Pb initial concentration 100 mg/L, Fe3O4/RGO dose 0.05 g, and contact time 30 min. Obtained results showed that the maximum adsorption capacity of Fe3O4/RGO for lead ion was 107.52 mg/g within 60 min of contact time. The adsorption behavior can be well described with the Langmuir isotherm and the pseudo-second-order models, indicating that the adsorption process was a monolayer and chemisorption adsorption.